Pola Pertumbuhan Rumput Laut pada Lokasi Tanam yang Berbeda di Perairan Pantai Pandawa, Bali - Bona Rizky Simanungkalit; Pande Gde Sasmita Julyantoro; Ayu Putu Wiweka Krisna Dewi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2024)
Seaweed cultivation is one of the leading commodities in the fishing sector and is still occupied by most coastal communities. One of the types of seaweed that can be cultivated is Eucheuma cottonii. One of the areas in Badung Regency that was once a place for seaweed cultivation is the South Kuta District, Badung Regency, Pandawa Beach, to be exact. The problem most often faced by seaweed cultivators is that seaweed cannot grow properly. The cause of seaweed not being able to grow properly occurs due to predators eating the seaweed thallus. Therefore, a study was conducted to determine the appropriate location on the Pandawa Beach for the cultivation of seaweed Eucheuma cottonii. The research method was carried out by planting Eucheuma cottonii seaweed in 3 different locations seen from the distance from the tourism position (water sport) in the waters of Pandawa Beach, first location in the water sport area, second location is 100 m to the west of the one location, third location is 100 m to the west of two location. The results of this study indicate that the average weight of seaweed at location 1 in the first to sixth week range 119,6 g – 399,7 g, location 2 range 121,80 g – 413,5 g, and at location 3 it ranged 123,35 g – 430,75 g. The Growth Rate (SGR) at Location 1 is 3,3%, Location 2 is 3,37%, and Location 3 is 3,47.%.